2002
DOI: 10.1159/000064040
|View full text |Cite
|
Sign up to set email alerts
|

Presence on human chromosome 10 of omeprazole-sensitivity gene whose product mediates CYP1A1 induction

Abstract: Previously, we showed that CYP1A1 expression can be induced by omeprazole (OP) in the human cell line HepG2, but not in the mouse cell line Hepa-1. Now we show induction of CYP1A1 by α-naphthoflavone (αNF) in Hepa-1 cells. This induction was inhibited by the tyrosine kinase inhibitor herbimycin A, but not by the aromatic hydrocarbon (Ah)-receptor antagonist PD98059, suggesting the presence of a ligand-independent signal-transduction pathway in the mouse cell line too. We utilized the lack of CYP1A1 induction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The species-specific differences in AhR activation by OME are thought to result from intracellular environment but not AhR itself (Kikuchi et al, 2002). The insensitivity to OME in mouse hepatocyte and OME reactivity of mouse AhR expressed in yeast agreed with this theory (Dzeletovic et al, 1997), and were reconfirmed in this study.…”
Section: Discussionsupporting
confidence: 78%
“…The species-specific differences in AhR activation by OME are thought to result from intracellular environment but not AhR itself (Kikuchi et al, 2002). The insensitivity to OME in mouse hepatocyte and OME reactivity of mouse AhR expressed in yeast agreed with this theory (Dzeletovic et al, 1997), and were reconfirmed in this study.…”
Section: Discussionsupporting
confidence: 78%
“…SB203580 Suppresses CYP1A1-mRNA Induction by Omeprazole-Kikuchi et al (27) showed that omeprazole induced CYP1A1-mRNA in a ligand-independent manner, and that the gene(s) that mediate its induction are present on human chromosome 10p (27). The induction of CYP1A1-mRNA by omeprazole was not suppressed by the AhR antagonist PD98059, suggesting the existence of a ligand-independent signaling pathway (Fig.…”
Section: Sb203580 Does Not Suppress In Vitro Ahrmentioning
confidence: 93%
“…Therefore, PI compounds are not acting as simple AhR antagonists. Kikuchi et al (27,33) have shown that omeprazole, an inhibitor of H ϩ /K ϩ -ATPase, activates AhR in a ligand-independent way. Our Fig.…”
Section: Sb203580 Does Not Suppress Translocation Of Ahr To the Nuclementioning
confidence: 99%
“…However, the PTK pathway appears to be unrelated to this interspecies difference because the tyrosine 320 residue is conserved in mouse and human AhRs. By fusing mouse and human hepatoma cells, a gene locus was assigned as a humanspecific gene responsible for CYP1A1 induction by OME (Kikuchi et al, 2002). However, specific genes exhibiting response to OME have not been identified.…”
Section: Introductionmentioning
confidence: 99%